2020
DOI: 10.1155/2020/2508952
|View full text |Cite
|
Sign up to set email alerts
|

Arctiin Antagonizes Triptolide‐Induced Hepatotoxicity via Activation of Nrf2 Pathway

Abstract: Triptolide (TP) is the most effective ingredient found in the traditional Chinese herbal Tripterygium wilfordii Hook F, and it is widely used in therapies of autoimmune and inflammatory disorders. However, the hepatotoxicity induced by TP has restricted its use in clinical trials. Arctiin is known as a protective agent against oxidative stress, and it exerts liver-protecting effect. This study was aimed at investigating the protective role of arctiin against TP-induced hepatotoxicity using in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Nrf2 or HO-1 inhibition abrogated the antiin ammatory effects exerted by various bioactive agents [55,56]. A recent study has revealed that arctiin prevented triptolide-induced acute live damage through activation of Nrf2 signaling [57]. Likewise, our ndings showed that the blockade of HO-1 reversed the suppression effect of arctiin on H9N2 viruselevated proin ammatory mediators (IL-6, TNF-α, COX-2, and PGE 2 ).…”
Section: Discussionsupporting
confidence: 54%
“…Nrf2 or HO-1 inhibition abrogated the antiin ammatory effects exerted by various bioactive agents [55,56]. A recent study has revealed that arctiin prevented triptolide-induced acute live damage through activation of Nrf2 signaling [57]. Likewise, our ndings showed that the blockade of HO-1 reversed the suppression effect of arctiin on H9N2 viruselevated proin ammatory mediators (IL-6, TNF-α, COX-2, and PGE 2 ).…”
Section: Discussionsupporting
confidence: 54%
“…Nrf2 or HO-1 inhibition abrogated the anti-inflammatory effects exerted by various bioactive agents [ 58 , 59 ]. A recent study has revealed that arctiin prevented triptolide-induced acute live damage through activation of Nrf2 signaling [ 60 ]. Likewise, our findings showed that the blockade of HO-1 reversed the suppression effect of arctiin on H9N2 virus-elevated proinflammatory mediators (IL-6, TNF-α, COX-2, and PGE 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR155, a regulator of the Nrf2 antioxidant pathway, was significantly activated and then inhibited the activity of the Nrf2 pathway in TP-induced hepatotoxicity (Li et al, 2021a). TP indeed decreased the protein expressions of the Nrf2 pathway including HO-1, NQO1, and Nrf2 associated with the oxidative stress pathway (Zhou et al, 2020). And a study found that TP-induced oxidative stress and cell damage in HepG2 cells could be aggravated by Nrf2 knockdown or counteracted by overexpression of Nrf2 (Li et al, 2014b).…”
Section: Triptolide (Tp)-induced Liver Injurymentioning
confidence: 98%